Impactos do tipo de manejo de plantas invasoras nos microrganismos do solo em plantio de restauração florestal - Parré, Fernando Martins (Universidade Federal de São Carlos, 2020)
The impact of invasive species management in forest restoration systems affects the communities of microorganisms in the soil and litter. They are fundamental for carrying out ecosystem functions, which guarantee the regeneration and functioning of ecosystems. The objective of this research was to test whether there was a difference between the quantity and activity of soil microorganism communities in the mechanical and chemical treatments of invasive plants in a forest restoration plantation, comparing them with each other and with a forest restoration plantation, over 11 months. We performed soil and litter collections in a restoration plantation submitted to two invasive plant management treatments: mechanical control (brushcutter) and chemical control (periodic use of glyphosate and clethodim), and in a forest fragment. We carried out analyzes of soil microbial carbon biomass (BMC) and basal soil respiration (RBS), calculated the soil metabolic coefficient (qCO2) and quantified the soil microorganisms using qPCR in real time. To measure the litter decomposition´s rate, we installed litter bags that were evaluated for 11 months. Through analysis of variance, t tests and mixed models, we verified that there is a difference between the areas subjected to mechanical or chemical control of invasive plants and that these areas differ, in some situations, from the preserved forest. In the restoration areas, there was an initial peak of activity in the soil microorganism communities, in response to the disturbance caused by the managements. In the qPCR analysis, the amount of bacteria in the soil was lower in chemical treatment than in mechanical treatment. The peak of activity in response to treatment was less pronounced for mechanical treatment compared to chemical treatment, analyzing the RBS, BMC and qCO2 curves. Twenty days after both treatments, there was a decrease in indicative variables of microbial activity in the soil. The mechanical treatment indicated rebalancing of the activity curves in mean values above zero at the end of the study, while the chemical treatment, which also showed this tendency to rebalance the curves, had mean values close to zero, indicating almost inactivity of the community at the end of the same period. These results indicate that chemical treatment was harmful to soil microbiological communities in the long term, with mechanical treatment ending with values more similar to those of the forest fragment. The decomposition rates of the mechanical treatment and the fragment were similar. The chemical treatment ended with the lowest volume of litter decomposed in the studied period. The chemical management of invasive plants was harmful to soil microorganism communities, leading to a lower decomposition rate. Thus, the use of mechanical management of invasive plants is less aggressive to soil microbial communities and positively influences the speed of soil biota regeneration, promoting forest restoration more efficiently.
Impacts of invasive plant management type on soil microorganisms in forest restoration planting
Keywords: Microrganismos do solo; Agrotóxico; Restauração vegetal; Soil microorganisms; Pesticides; Forest restauration; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA